Bioengineering : proceedings of eighth Northeast conference, March 27-28, 1980, Massachusetts Institute of Technology, Cambridge, Massachusetts - Paul, Igor (Pergamon Press, 1980)
Bioengineering: Proceedings of the Eighth Northeast Conference focuses on the discussion of scientific programs, methodologies, experiments, and contributions to the advancement of bioengineering, such as in the field of medicine. The book is composed of literature of various authors who have worked diligently in the field of bioengineering. The text starts by discussing the conditions, situations, and experiments on how the human bones and other internal organs react if subjected to stress, fatigue, and other factors. The properties, composition, and reactions of these body parts to different.